USING SUMMARIZATION TECHNIQUE IN TEACHING READING COMREHENSION TO THE SECOND GRADERS OF MTSN PUCANGLABAN - Fitriana, Maylia Wilda (Lingua Scientia, 2013)
Abstract: Many of students have difficulties in learning English, especially in reading comprehension. They do not understand about meaning in the text. Some of them cannot read and spell it correctly whether in spoken form or written form. They also lack in vocabulary. As an English teacher, we have to be able to find an interesting strategy or method in teaching English especially in reading comprehension. So, if we have some strategies or method, the students will be interested and not feel bored with our teaching in English. The teacher should be able to find and use the appropriate strategy or method which is suitable with the studentsâ condition and the material. Based on the problems above, the writer is interested to find out the technique in reading comprehension. One of the techniques used in teaching reading comprehension is summarization technique for the second year students at MTsN Pucanglaban Tulungagung in the academic year 2012/2013. The purpose of the study were to:1) know the studentsâ reading comprehension before being taught using summarization technique,Â 2) know the studentsâ reading comprehension after being taught using summarization technique, 3) know the difference between studentsâ reading comprehension before and after using summarization technique. The result showed that the studentsâ mean score in teaching reading comprehension before they are taught using summarization technique was 84.37. While the studentsâ mean score after they are taught using summarization technique was 90.43. By comparing significant level in t table at 0.05, it is known that t count is bigger than t table. It means that Ha which states that there is significant influence of using summarization technique in teaching reading comprehension of the second years of MTsN Pucanglaban Tulungagung is accepted. Whereas Ho which states that there is no significant influence of using summarization technique in teaching reading comprehension of the second years of MTsN Pucanglaban Tulungagung is rejected. In other words, summarization technique can be used as an alternative to teach reading comprehension to the students at JHS level.Keywords: Teaching, Reading Comprehension, Summarization Technique